2012
DOI: 10.3892/mmr.2012.1028
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopaminergic/GABAergic genes with attention deficit hyperactivity disorder in children

Abstract: Abstract. Attention deficit hyperactivity disorder (ADHD) is the most commonly diagnosed neurobehavioral disorder in children and adolescents; however, its etiology is unknown. In this study, we investigated the association of five polymorphisms in dopaminergic/GABAergic genes with ADHD using polymerase chain reaction-restriction fragment length polymorphism in a group of 54 children with ADHD and 67 healthy controls. The distribution of AA genotype and A allele frequencies of rs5320 in the dopamine beta-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the cortex, inhibitory GABAergic interneurons are modifying and directing neuronal activity, and interneuronal dysfunction is acknowledged to play an important role in the etiology of several psychiatric diseases, including ADHD (Wang et al, 2012) and ASD (Gao and Penzes, 2015;Hashemi et al, 2017). Oxidative stress can cause cellular damage of GABAergic interneurons, leading to decreased neuronal activity (Sakurai and Gamo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the cortex, inhibitory GABAergic interneurons are modifying and directing neuronal activity, and interneuronal dysfunction is acknowledged to play an important role in the etiology of several psychiatric diseases, including ADHD (Wang et al, 2012) and ASD (Gao and Penzes, 2015;Hashemi et al, 2017). Oxidative stress can cause cellular damage of GABAergic interneurons, leading to decreased neuronal activity (Sakurai and Gamo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, both ADHD and ASD involve synaptic mechanisms. Genes in dopaminergic [55], serotoninergic [53], glutamatergic [56,57] and GABAergic [58,59] systems have been implicated in both disorders. Variants in SHANK3-NLGN4-NRXN1 postsynaptic density genes were found in ASD [60].…”
Section: Biologicalmentioning
confidence: 99%
“…Although the etiology and pathophysiology of ADHD remain unclear, some data support the interaction between genetic and environmental factors ( Wang et al, 2012 ; Sun et al, 2018 ). In particular, Kwon and coauthors have shown an association between GABAB3 gene polymorphisms and ADHD in children ( Kwon et al, 2017 ).…”
Section: Gaba a Rs And Neuropsychiatric Disordersmentioning
confidence: 99%